Penggunaan Penulisan pada Papan Nama di Desa Air Molek Kecamatan Pasir Penyu Kabupaten Indragiri Hulu - Elsa Agustine; Jamilin Tinambunan (UIR Press, 2022)
The writing error found on the nameplate is one example that proves that the writing on the nameplate does not pay attention to the writing rules of the General Indonesian Spelling Guidelines (PUEBI). The purpose of the research is to obtain data and information collected to be described, analyzed, and interpreted systematically so that a true picture can be obtained of the rules for writing shop signboards in Air Molek Village, Pasir Turtle District, Indragiri Hulu Regency, Riau Province. The theory used is the theory of the Center for Language Development and Development of the Ministry of National Education of the Republic of Indonesia (2017), Sugono (2007), and Dahlan (2007). The methodology used is the method of content analysis, using documentation techniques and hermeneutic techniques. In total, there are 53 nameplates, 49 incorrect writings with errors such as the use of capital letters, the use of punctuation marks, abbreviations, and word writing. While the correct writing is 4 nameplates, so the writing is categorized as not good because many are not in accordance with the General Guidelines for Indonesian Spelling (PUEBI).